2009
DOI: 10.1017/s104161020900903x
|View full text |Cite
|
Sign up to set email alerts
|

The Vellore screening instruments and strategies for the diagnosis of dementia in the community

Abstract: The patient screen and the informant version are short culture- and education-fair instruments. They reduce false positive rates, when used in combination in the community.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 22 publications
0
23
0
1
Order By: Relevance
“…The recently developed Vellore Screening Instrument for Dementia seems promising, but with 10 cognitive and 10 informant items it may be too long for routine use. Furthermore, its only community validation to date was on a sample of only 101 participants, three of whom were diagnosed with dementia (Stanley et al , 2009). …”
Section: Introductionmentioning
confidence: 99%
“…The recently developed Vellore Screening Instrument for Dementia seems promising, but with 10 cognitive and 10 informant items it may be too long for routine use. Furthermore, its only community validation to date was on a sample of only 101 participants, three of whom were diagnosed with dementia (Stanley et al , 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Stanley et al [20] reported the unacceptable false-positive rates of a screening instrument for dementia when used in the community as compared to hospital use. Chan et al [21] studied whether a screening questionnaire for parkinsonism yielded similar results when used in the hospital and community setting in Australia, and found that results do tend to differ between the two.…”
Section: Discussionmentioning
confidence: 99%
“…Using the 10/66 dementia research group algorithm, a higher prevalence rate for dementia was found (urban Chennai: 7.5 % and rural Vellore: 10.6 %) (Llibre Rodriguez et al 2008). Vellore screening instrument was developed after employing the 'activities of daily living', which are not influenced by education and culture and can reduce the false-positive rates in community studies (Stanley et al 2009). …”
Section: Dementiamentioning
confidence: 99%